2016
DOI: 10.1530/erc-16-0379
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive follicular thyroid neoplasm with papillary-like nuclear features

Abstract: Recently, it was proposed that some papillary thyroid carcinomas (PTC) will no longer be termed 'cancer' and are christened as 'noninvasive follicular thyroid neoplasm with papillary-like nuclear features' (NIFTP). As this is a recent definition, little information is available about NIFTP. The objective of this study was to report the frequency, ultrasonographic appearance, cytology result and long-term evolution of cases of NIFTP seen at our institution. We excluded tumours ≤1 cm. The sample consisted of 129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 12 publications
6
80
0
Order By: Relevance
“…Continued)There is only one other study that examined the sonographic features of NIFTP 6. In this study, cases of NIFTP on ultrasound were found to be of "low suspicion for malignancy" according to Haugen et al's American Thyroid Association pattern classifications 1,6. In their study NIFTP more commonly displayed wider-than-tall shape, smooth borders, solid type nodules and lack of calcifications, findings similar to our study.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Continued)There is only one other study that examined the sonographic features of NIFTP 6. In this study, cases of NIFTP on ultrasound were found to be of "low suspicion for malignancy" according to Haugen et al's American Thyroid Association pattern classifications 1,6. In their study NIFTP more commonly displayed wider-than-tall shape, smooth borders, solid type nodules and lack of calcifications, findings similar to our study.…”
supporting
confidence: 86%
“…In this study, cases of NIFTP on ultrasound were found to be of "low suspicion for malignancy" according to Haugen et al's American Thyroid Association pattern classifications 1,6. This study did not compare NIFTP to other benign or malignant entities, nor examine Doppler flow pattern or grade, findings that add more information to the literature as reported in our study(Table 3) 6. This study did not compare NIFTP to other benign or malignant entities, nor examine Doppler flow pattern or grade, findings that add more information to the literature as reported in our study(Table 3) 6.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Ultrasound [16][17][18] and cytologic studies [19][20][21][22][23][24] useful in the differentiation of NIFTP from PTC are summarized in Table I.…”
mentioning
confidence: 99%